Methods to Identify Immune Cells in Tissues With a Focus on Skin as a Model. Issue 7 (13th July 2022) - Murphy, Peter R.; Narayanan, Divyaa; Kumari, Snehlata
Abstract: The skin protects our body from external challenges, insults, and pathogens and consists of two layers, epidermis and dermis. The immune cells of the skin are an integral part of protecting the body and essential for mediating skin immune homeostasis. They are distributed in the epidermal and dermal layers of the skin. Under homeostatic conditions, the mouse and human skin epidermis harbors immune cells such as Langerhans cells and CD8 + T cells, whereas the dermis contains dendritic cells (DCs), mast cells, macrophages, T cells, and neutrophils. Skin immune homeostasis is maintained through communication between epidermal and dermal cells and soluble factors. This communication is important for proper recruitment of immune cells in the skin to mount immune responses during infection/injury or in response to external/internal insults that alter the local cellular milieu. Imbalance in this crosstalk that occurs in association with inflammatory skin disorders such as psoriasis and atopic dermatitis can lead to alterations in the number and type of immune cells contributing to pathological manifestation in these disorders. Profiling changes in the immune cell type, localization, and number can provide important information about disease mechanisms and help design interventional therapeutic strategies. Toward this end, skin cells can be detected and characterized using basic techniques like immunofluorescence, immunohistochemistry, and flow cytometry, and recently developed methods of multiplexing. This article provides an overview on the basic techniques that are widely accessible to researchers to characterize immune cells of the skin. © 2022 The Authors. Current Protocols published by Wiley Periodicals LLC.